2019
DOI: 10.1039/c8mo00244d
|View full text |Cite
|
Sign up to set email alerts
|

Dual-network sparse graph regularized matrix factorization for predicting miRNA–disease associations

Abstract: Combined dual network, L2,1-norm and graph regularized matrix factorization for predicting miRNA–disease associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Finally, the AUCs of GRL 2, 1 -NMF are higher than those of some excellent models. Note that DNSGRMF [53], which also predicts miRNA-disease connections, is a graph regularized method similar to GRL 2, 1 -NMF. Both methods decompose the original matrix Y into two matrices W and H, and then we can acquire a recovery matrix Y * = W * H. It is worth noting that GRL 2, 1 -NMF is based on nonnegative factorization, while DNSGRMF is based on graph regularized matrix factorization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the AUCs of GRL 2, 1 -NMF are higher than those of some excellent models. Note that DNSGRMF [53], which also predicts miRNA-disease connections, is a graph regularized method similar to GRL 2, 1 -NMF. Both methods decompose the original matrix Y into two matrices W and H, and then we can acquire a recovery matrix Y * = W * H. It is worth noting that GRL 2, 1 -NMF is based on nonnegative factorization, while DNSGRMF is based on graph regularized matrix factorization.…”
Section: Discussionmentioning
confidence: 99%
“…3 Flow chart of GRL2,1-NMF leveraging the geometric structure of the data [56]. The L 2, 1 -norm was added to increase the disease matrix sparsity and eliminate unattached disease pairs [30,52,53]. The optimization problem of GRL 2, 1 -NMF can be formularized as follows:…”
Section: Standard Nmfmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, they provide scoring schemes that can create correlation sets of high and medium credibility. L − norm and Gaussian interaction profile (GIP) kernel to improve the prediction ability [25]. In addition, considering the nearest neighbor information of the miRNA and the disease,…”
Section: Yin Et Al Proposed a New A Computational Model Of Matrix Dementioning
confidence: 99%
“…The discovery of extensive transcription of large RNA transcripts which do not code for proteins, termed long noncoding RNAs (lncRNAs), provides a new perspective in understanding the centrality of RNA in gene regulation (Rinn and Chang, 2012). Evidences have shown that lncRNAs are key regulators for many cellular functions, including splicing, gene regulation, and hormone-like activity (Gao et al, 2019a;Mongelli et al, 2019). Moreover, the dysregulation of lncRNAs has been proved to be closely related with various human diseases, such as types of cancer, neurological as well as cardiovascular diseases (Feng et al, 2018;Zhang et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%